Winter Notes on Summer Impressions - Dostoyevsky, Fyodor; Translated by FitzLyon, Kyril (London Alma Classics Ltd., 2013)
In June 1862, Dostoevsky left Petersburg on his first excursion to Western Europe. Ostensibly making the trip to consult Western specialists about his epilepsy, he also wished to see firsthand the source of the Western ideas he believed were corrupting Russia. This book presents the impressions of what he saw.
One of Dostoevsky's lesser known essays, with an extensive section on his life and works In June 1862, Dostoevsky left Petersburg on his first excursion to Western Europe. Ostensibly making the trip to consult Western specialists about his epilepsy, he also wished to see firsthand the source of the Western ideas he believed were corrupting Russia. Over the course of his journey he visited a number of major cities, including Berlin, Paris, London, Florence, Milan, and Vienna. His record of the trip is the chrysalis out of which many elements of his later masterpieces developed.
Include Notes.
Keywords: Travel -- Europe -- Authors, Russian